Additive manufacturing of TPU/C and PVDF/graphene composites with adjustable mechanical and conductive properties for sensor applications - Ana C. Pinho; Ana P. Piedade (Results in Engineering)
Polymers are usually not electrical conductors, but polymer-based composites reinforced with conductive materials can overcome this limitation, opening new possibilities in producing innovative and useful components. Their application in industry has been greatly enhanced by their applications in smart sensors, such as optical sensors, chemical sensors and biosensors. Currently, additive manufacturing technologies are used to produce different polymeric-based components. However, the processing parameters may alter the properties of the materials, especially if the processing technology involves temperature, such as in the case of fused filament fabrication. The present work investigated two filaments FilaFlex®, a composite made of polyurethane reinforced with carbon fibres, and Koltron G1®, a composite with a matrix of poly(vinyl difluoride) and graphene reinforcement. The pre- and post-printed composites were characterized regarding their chemical structure, thermal stability, and surface morphology. The mechanical performance and electric conductive properties were also simultaneously evaluated during static, dynamic and cyclic tensile tests. The results showed that the conductivity decreases after printing, as FilaFlex® and Koltron G1® filaments present electrical conductivity of 33 and 30 μS⋅mm-1, respectively, while their corresponding printed specimens present electrical conductivity of 11 (FilaFlex®) and 15 μS⋅mm-1 (Koltron G1®). The dynamic tensile strength tests performed on both filaments and 3D-printed specimens showed that overall, FilaFlex® displayed greater electrical stability and lower electrical resistance when compared with Koltron G1®. Tensile cyclic tests exhibited a response pattern for the electrical resistance of the FilaFlex® as a function of the load-unload cycle with a very constant variation, between maximal and minimum values, of around 20 Ω. Koltron G1® presented an entirely different profile with variations of 2000 Ω occurring during the cycles. To the best of our knowledge, this is one of the very few works where the mechanical and conductive properties were simultaneously evaluated during static, dynamic and cyclic tensile tests. This aspect is a significant innovation of the study, which aims to evaluate the suitability of these CPC and processing technology for the production of customisable sensors.